Social Media Da'wah Literacy on the West Java Saber Hoaks Program - Imron Rosyidi; Zaenal Mukarom; Rif'at Fatkhurrohman Jaelani (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2021)
Hoax or false information is a problem and one of the impacts of the unwise use of social media. The spread of hoaxes on social media can potentially break the unity and trigger religious conflict. In response to these problems, West Java Saber Hoaks was formed to suppress and prevent the spread of hoaxes on social media. The purpose of this study is to reveal: (1) Jabar Saber Hoaks' efforts in preventing hoaxes; and (2) literacy of social media da'wah by Jabar Saber Hoaks. This study uses a case study method with a qualitative approach. Based on the study results, the following findings were obtained: (1) There were four efforts made by West Java Saber Hoaks to prevent hoaxes, namely opening a complaint service and monitoring content that has the potential to be a hoax, clarifying information, and providing literacy. (2) Social media da'wah literacy by West Java Saber Hoaks is carried out using preventive measures and information verification. From the results of this study, there are significant and recommendations, namely: (1) There is a need for mainstreaming social media literacy. (2) There is a need for preventive da'wah efforts on social media to ward off hoax information.Hoaks atau false information merupakan problematika dan salah satu dampak yang ditimbulkan dari penggunaan media sosial yang kurang bijak. Penyebaran hoaks di media sosial dapat berpotensi memecah persatuan dan memicu konflik keagamaan. Menyikapi persmasalahan tersebut, Jabar Saber Hoaks dibentuk untuk menekan dan menangkal penyebaran hoaks di media sosial. Tujuan dari studi ini ialah untuk mengungkap: (1) Upaya Jabar Saber Hoaks dalam menangkal hoaks; dan (2) Literasi dakwah media sosial oleh Jabar Saber Hoaks. Studi ini menggunakan metode studi kasus dengan pendekatan kualitatif. Berdasarkan hasil studi, didapatkan temuan berikut: (1) Ada empat upaya yang dilakukan Jabar Saber Hoaks dalam menangkal hoaks, yaitu membuka layanan aduan, memantau konten yang beprotensi hoaks, mengklarifikasi informasi dan memberikan literasi. (2) Literasi dakwah media sosial oleh Jabar Saber Hoaks dilakukan dengan cara upaya preventif dan verifikasi informasi. Dari hasil studi ini ada signifikasi dan rekomendasi, yaitu: (1) Perlu adanya mainstreaming literasi media sosial. (2) Perlu adanya uapaya dakwah preventif di media sosial untuk menangkal informasi hoaks.